A Spontaneously Necrotic Wilms' Tumor Mimicking Renal Abscess: A Tricky Diagnosis not to Miss. Issue 2 (18th March 2021) - Sevrin, François; Rocourt, Nathalie; Leroy, Xavier; Coulomb-L'Hermine, Aurore; Sudour-Bonnange, Hélène
Abstract : Wilms' tumor (WT) is the most common renal malignancy in children. Its clinical and radiologic presentation may mimic other pediatric renal diseases, including pyonephrosis or renal abscess. The authors report a case of a 3-year-old girl presenting with pyelonephritis and right renal mass suggestive of a renal abscess, not responding to antibiotics. Further investigations were conducted, including a percutaneous renal needle core biopsy. A stage I fully necrotic WT was finally diagnosed. This amazing case of a fully necrotic WT at diagnosis demonstrates the importance of anatomopathologic analyses in pediatric renal masses, even when the infection is suspected.